A Naturalistic Evaluation of Change in Antidepressant Prescription in Patients With Affective and Anxiety Disorders in a Tertiary Care Hospital of India. Issue 1 (February 2018) - Patil, Amol; Sahoo, Swapnajeet; Garg, Gaurav; Grover, Sandeep
Abstract: Background: Although many studies have evaluated prescription patterns, there is lack of information on the choice of antidepressants among patients who do not respond antidepressants. Similarly, information on switching strategies is also limited. This naturalistic study aimed to evaluate the switching strategies and preferred antidepressants by the psychiatrists among patients who do not respond to or who are not able to tolerate an antidepressant. Methods: A cross-sectional observational study design was followed. Patients diagnosed with affective and anxiety disorders, who were recommended a change in antidepressant, were recruited. Details of antidepressant before switching, antidepressants considered at the time of switching, coprescription advised at the time of switching, reasons considered for switching, and strategy advised at the time of switching were noted down. Results: A total of 102 patients were recruited. The most common change strategy was selective serotonin reuptake inhibitor (SSRI) to a serotonin norepinephrine reuptake inhibitor (SNRI) (N = 42; 41.17%), and this was followed by SSRI to SSRI (N = 18; 17.64%) and SNRI to SSRI (N = 10; 9.8%). In majority of the patients (N = 79; 77.45%) cross-taper of older antidepressant with gradual increase in dose of newer antidepressants was followed. About 44.1% of the patients were on adjuvant medications at the time of considering change in antidepressants, and 37.25% of the patients were additionally started on some adjuvant medications during the change of antidepressants. Conclusions: The present study suggests that the most common strategy followed during change of antidepressant is from SSRI to SNRI and this is followed by SSRI to SSRI and SNRI to SSRI. Cross-taper switching strategy along with the use of adjuvant medications like benzodiazepines during the process of switching is most commonly followed.